Humoral Immunity vs. Salmonella - Takaya, Akiko; Yamamoto, Tomoko; Tokoyoda, Koji (Frontiers in Immunology, 2020)
In primary infection with Salmonella, it has been reported—without consideration of Salmonella's functions—that humoral immunity plays no role in the clearance of bacteria. In fact, Salmonella targets and suppresses several aspects of humoral immunity, including B cell lymphopoiesis, B cell activation, and IgG production. In particular, the suppression of IgG-secreting plasma cell maintenance allows the persistence of Salmonella in tissues. Therefore, the critical role(s) of humoral immunity in the response to Salmonella infection, especially at the late phase, should be re-investigated. The suppression of IgG plasma cell memory strongly hinders vaccine development against non-typhoidal Salmonella (NTS) because Salmonella can also reduce humoral immune memory against other bacteria and viruses, obtained from previous vaccination or infection. We propose a new vaccine against Salmonella that would not impair humoral immunity, and which could also be used as a treatment for antibody-dependent autoimmune diseases to deplete pathogenic long-lived plasma cells, by utilizing the Salmonella's own suppression mechanism of humoral immunity.